The Influence of Hierarchy on Idea Generation and Selection in the Innovation Process - Keum, Dongil D.; See, Kelly E. (Organization Science, 2017)
The link between organizational structure and innovation has been a longstanding interest of organizational scholars, yet the exact nature of the relationship has not been clearly established. Drawing on the behavioral theory of the firm, we take a process view and examine how hierarchy of authority—a fundamental element of organizational structure reflecting degree of managerial oversight—differentially influences behavior and performance in the idea generation versus idea selection phases of the innovation process. Using a multimethod approach that includes a field study and a lab experiment, we find that hierarchy of authority is detrimental to the idea generation phase of innovation, but that hierarchy can be beneficial during the screening or selection phase of innovation. We also identify a behavioral mechanism underlying the effect of hierarchy of authority on selection performance and propose that selection is a critical organizational capability that can be strategically developed and managed through organizational design. Our investigation helps clarify the theoretical relationship between structure and innovation performance and demonstrates the behavioral and economic consequences of organizational design choice. The online appendix is available at https://doi.org/10.1287/orsc.2017.1142 .